The Effect of the Creative Problem Solving Model Assisted by Mind Mapping on Problem-Solving Ability of Grade VII Students at SMPN 7 Padang - Kessy Kessy Putri Mulya; Aulia Azhar; Tuti Lestari; Ade Sazaliana (Al-Alam: Islamic Science Education Journal, 2026)
This study aims to describe the implementation of learning, analyze its effect, and explore students’ responses to the application of the Creative Problem Solving (CPS) model assisted by Mind Mapping in improving the problem-solving skills of seventh-grade students at SMPN 7 Padang.This research employed a quasi-experimental design with a Non-equivalent Control Group Design model. The sample was selected using purposive sampling, with class VII.6 as the experimental group and class VII.8 as the control group, each consisting of 32 students. The research instruments included essay tests on problem-solving skills, observation sheets on the implementation of learning, and student response questionnaires. The findings showed that the implementation of learning by the teacher reached an average of 98% and by students 88%, both categorized as very good. Hypothesis testing using a parametric t-test indicated that the data were normally distributed and homogeneous, with a result of t-count = 5.88 > t-table = 1.99, so H1 was accepted. This indicates that the CPS model assisted by Mind Mapping has a significant effect on problem-solving skills. Students’ responses were categorized as very positive, with an average percentage of 82.45%.It can be concluded that the Creative Problem Solving learning model assisted by Mind Mapping has a positive and significant effect on the problem-solving skills of seventh-grade students at SMPN 7 Padang.